Life Expectancy Is Poor in Patients with Diffuse Idiopathic Skeletal Hyperostosis-Related Pyogenic Vertebral Osteomyelitis - Kentaro Yamada; Makoto Ieguchi; Shinji Takahashi; Hiroaki Nakamura (Spine Surgery and Related Research, 2022)
Introduction: Pyogenic vertebral osteomyelitis (PVO) is an uncommon but life-threatening infectious disease. Diffuse idiopathic skeletal hyperostosis (DISH) is an age-related disorder and sometimes problematic in terms of spinal instability or high mortality, especially in cases of DISH-related fracture. Meanwhile, no reports have focused on the impact of DISH on the clinical outcomes after treatment for PVO. We hypothesized that PVO occurring at DISH-related segments might contribute to poor clinical results or high mortality rates. The purpose of this study was to investigate the impact of DISH on mortality after treatment for PVO in a retrospective cohort study. Methods: This study involved patients who were hospitalized and treated for PVO at a single institution. DISH-related PVO was defined as PVO within a segment ossified by DISH or PVO at the neighboring intervertebral level of the segment ossified by DISH. Differences in mortality between patients with DISH-related and non-DISH-related PVO were investigated. Results: This study included 55 patients. DISH-related PVO was observed in 13 patients. The mortality rate was significantly higher in patients with DISH-related PVO than in those with non-DISH-related PVO (62% and 23%, respectively; p=0.016). Propensity score-adjusted analysis showed that DISH-related PVO was an independent risk factor for mortality (adjusted hazard ratio, 2.79; p=0.034). The survival probability was significantly shorter in patients with DISH-related PVO than in those with non-DISH-related PVO (p=0.006). PVO in which the intravertebral body was the center of involvement was significantly more common in DISH-related PVO than in non-DISH-related PVO (38% and 5%, respectively; p=0.006). Conclusions: DISH-related PVO was associated with a higher mortality rate and shorter life expectancy than non-DISH-related PVO. Similar to advanced age, PVO at the segment ossified by DISH should be recognized as a risk factor for mortality when choosing the optimal treatment strategy.